2008
DOI: 10.1103/physrevc.78.035204
|View full text |Cite
|
Sign up to set email alerts
|

ηphotoproduction on the proton in a chiral constituent quark approach via a one-gluon-exchange model

Abstract: A formalism based on a chiral quark model (χQM) approach complemented with a one-gluon exchange model, to take into account the breakdown of the SU (6) ⊗ O(3) symmetry, is presented.The configuration mixing of wave functions for nucleon and resonances are derived. With few adjustable parameters, differential cross-section and polarized beam asymmetry for the γ p → η p process are calculated and successfully compared with the data in the centre-of-mass energy range from threshold up to 2 GeV. The known resonanc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

17
82
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 46 publications
(101 citation statements)
references
References 74 publications
17
82
2
Order By: Relevance
“…2 The effects of D 15 (2080) can be expected in γp → ηp taking into account the mixing between η ′ and η. A recent quark model study of η photoproduction in the high energy region has reported effects from D 15 (2080) [22,23]. Evidence of D 15 (2080) was also found by a partial wave analysis of the η photoproduction data from CB-ELSA [36] in the BonnGatchina (BnGa) model [37].…”
Section: A Parametersmentioning
confidence: 89%
See 1 more Smart Citation
“…2 The effects of D 15 (2080) can be expected in γp → ηp taking into account the mixing between η ′ and η. A recent quark model study of η photoproduction in the high energy region has reported effects from D 15 (2080) [22,23]. Evidence of D 15 (2080) was also found by a partial wave analysis of the η photoproduction data from CB-ELSA [36] in the BonnGatchina (BnGa) model [37].…”
Section: A Parametersmentioning
confidence: 89%
“…The chiral quark model has been well developed and widely applied to meson photoproduction reactions [16][17][18][19][20][21][22][23][24][25][26][27]. The details about the model can be found in [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…As a consequence, configuration mixings would occur, and an analytic solution cannot be achieved. To take into account the breaking of that symmetry, an empirical way [83,84] is to introduce a set of coupling strength parameters, C R , for each resonance amplitude,…”
Section: A Parametersmentioning
confidence: 99%
“…Since the quark-meson coupling is invariant under the chiral transformation, some of the low-energy properties of QCD are retained. The chiral quark model has been well developed and widely applied to meson photoproduction reactions [78][79][80][81][82][83][84][85][86][87][88]. Its recent extension to de- scribe the process of πN [89] andKN [42] scattering, and the charmed hadron strong decays [90][91][92] also turns out to be successful and inspiring.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it has predictive powers when exposed to experimental data, and information about the resonance structures can be extracted. The chiral quark model has been well developed and widely applied to meson photoproduction reactions [48,49,[56][57][58][59][60][61][62][63][64][65][66][67][68]. Recently, this model has been successfully extended to πN and KN reactions as well [43,[69][70][71].…”
Section: Introductionmentioning
confidence: 99%